PENERAPAN MAIN HEALING TECHNIQUE (MHT) UNTUK TERAPI BERHENTI MEROKOK SISWA MAN 2 KOTA BANDUNG - Asep Encu; Heni Hasanah (Kantor Kementerian Agama Kabupaten Pangandaran bekerja sama dengan Asosiasi Profesi Perkumpulan Manajer Pendidikan Islam (Perma Pendis) Indonesia., 2020)
This study aims to determine the decrease in the number of smokers for students of MAN 2 Bandung through the application of the Main Healing Technique (MHT) and to know the steps of its application. The background of this research is the observation result of BP teachers which shows that there are students who have difficulty quitting smoking outside of school hours. The research was conducted in 2 cycles. Initial actions that have been taken are the optimization of School Health Business Education and the establishment of anti-smoking ambassadors in each class as well as counseling on the dangers of smoking. And the results from 360 male students obtained that 54.5% of students had ever smoked and 45.5% had never smoked. Students who had smoked were then diagnosed with a smokerlyzer device by the local Puskesmas staff and 17.8% of students were detected as having started addiction and smoking every day. Then the first cycle research was carried out by applying the Main Healing Technique (MHT) in collaboration with the Psychotherapy Sufism Study Program at UIN Sunan Gunung Djati Bandung en masse. Then the Main Healing Technique (MHT) action was performed again in the second cycle in groups. The results showed a decrease in the number of students who smoked. Students who used to smoke every day were 9.9% but after MHT it became 1.9%. Students who occasionally smoked from 15.7% to 0.42%. So the results of the study conclude that the application of the Main Healing Technique (MHT) can be used as an alternative for therapy for students to be freed from smoking habits.